2006
DOI: 10.1073/pnas.0510410103
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuregulin–ErbB4 interactions on the proliferation and organization of cells in the subventricular zone

Abstract: Coordinated regulation of neuronal progenitor differentiation in the subventricular zone (SVZ) is a fundamental feature of adult neurogenesis. However, the molecular control of this process remains mostly undeciphered. Here, we investigate the role of neuregulins (NRGs) in this process and show that a NRG receptor, ErbB4, is primarily expressed by polysialylated neural cell adhesion molecule immature neuroblasts but is also detected in a subset of GFAP ؉ astroglial cells, ependymal cells, and Dlx2 ؉ precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 44 publications
9
133
1
Order By: Relevance
“…We then defined whether Cdk6 deficiency would also preferentially affect the proliferation of a particular subpopulation of precursors of the SVZ. Using Sox2 as a marker of type B cells in the SVZ [28,29], we first observed that the numbers of Sox2 þ /Ki-67 þ cells were not impaired in the absence of Cdk6 (Supporting Information Fig. 7).…”
Section: Cdk6 Selectively Regulates the Proliferation Of Neuronally Cmentioning
confidence: 99%
“…We then defined whether Cdk6 deficiency would also preferentially affect the proliferation of a particular subpopulation of precursors of the SVZ. Using Sox2 as a marker of type B cells in the SVZ [28,29], we first observed that the numbers of Sox2 þ /Ki-67 þ cells were not impaired in the absence of Cdk6 (Supporting Information Fig. 7).…”
Section: Cdk6 Selectively Regulates the Proliferation Of Neuronally Cmentioning
confidence: 99%
“…[8][9][10][11] ERBB4 plays a critical role in the development of the brain, and has been shown to directly influence the proliferation, organization and migration of cells in the rostral migratory stream. [12][13][14] There is now emerging evidence that the gene for ERBB4 also influences risk for schizophrenia, 15,16 especially when considered together with NRG1. 16 Moreover, there is evidence from postmortem mRNA studies for alterations in the levels of ERBB4 15 (as well as the ERBB3 coreceptor [17][18][19][20][21] ) in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Subventricular zone cells express several substrates for TACE proteolysis in addition to APP and TNFa (Doetsch et al, 2002;Ghashghaei et al, 2006;Stump et al, 2002). In fact, several TACE-cleaved EGFR proligands represent attractive candidates for TACE-mediated SVZ neurogenesis as well (Doetsch et al, 2002;Jin et al, 2004;Stump et al, 2002).…”
Section: Introductionmentioning
confidence: 99%